Predator-deterring alarm call sequences in Guereza colobus monkeys are meaningful to conspecifics - Schel, Anne Marijke; Candiottia, Agnès; Zuberbühler, Klaus (My University, 2010)
Guereza colobus monkeys, Colobus guereza, produce acoustically conspicuous vocalizations, the roars, in response to their main predators, leopards, Panthera pardus, and crowned eagles, Stephanoaetus coronatus. Roaring alarm utterances generally consist of the same basic call types but differ in overall structural composition. Leopards trigger roaring alarms containing many roaring sequences of only a few calls each, while eagles trigger few sequences with many calls each. To investigate whether conspecifics extract meaning from these structural differences, we played back leopard and eagle alarm call sequences and compared the monkeys’ responses in terms of their locomotor, gaze and vocal behaviour with their responses to the corresponding predator vocalizations. Locomotor responses did not differ between playback conditions; movement was always towards the simulated caller with no clear patterns in the vertical plane. Gaze direction, however, was highly predator specific. When hearing leopard-related stimuli, monkeys were significantly more likely to scan the area beneath them than when hearing eagle-related stimuli, which caused more scanning above. Vocal response rates to conspecific alarms were generally low but comparable with rates to the corresponding predators. If monkeys called, however, they produced the matching call sequences. Overall, our results showed that Guerezas discriminated between predator alarm call sequences produced by unfamiliar conspecifics and responded to them in predator-specific ways. Since the sequences were composed of the same basic call types, we concluded that the monkeys attended to the compositional aspects of these utterances.
Keywords: alarm call; Budongo Forest; Colobus guereza; Guereza colobus; perception advertisement; predation; predator deterrence; primate communication; semantic; syntax